Hip Morphology in Early-stage LCPD: Is There an Argument for Anatomic-specific Containment?. Issue 6 (12th July 2021) - Selberg, Courtney M.; Bram, Joshua T.; Carry, Patrick; Goldstein, Rachel Y.; Schrader, Tim; Laine, Jennifer C.; Kim, Harry K.W.; Sankar, Wudbhav N.
Abstract : Background: Early containment surgery has become increasingly popular in Legg-Calvé-Perthes Disease (LCPD), especially for older children. These procedures treat the proximal femur, the acetabulum, or both, and most surgeons endorse the same surgical option regardless of an individual patient's anatomy. This "one-surgery-fits-all" approach fails to consider potential variations in baseline anatomy that may make one option more sensible than another. We sought to describe hip morphology in a large series of children with newly diagnosed LCPD, hypothesizing that variation in anatomy may support the concept of anatomic-specific containment. Methods: A retrospective review of a prospectively collected multicenter database was conducted for patients aged 6 to 11 at diagnosis. To assess anatomy before significant morphologic changes secondary to the disease itself, only patients in Waldenström stages IA/IB were included. Standard hip radiographic measurements including acetabular index, lateral center-edge angle, proximal femoral neck-shaft angle (NSA), articulotrochanteric quartiles, and extrusion index (EI) were made on printed anteroposterior pelvis radiographs. Age-specific percentiles were calculated for these measures using published norms. Significant outliers (≤10th/≥90th percentile) were reported where applicable. Results: A total of 168 patients with mean age at diagnosis of 8.0±1.3 years met inclusion criteria (81.5% male). Mean acetabular index for the entire cohort was 16.8±4.1 degrees; 58 hips (34.5%) were significantly dysplastic compared with normative data. Mean lateral center-edge angle was 15.9±5.2 degrees at diagnosis; 110 (65.5%) were ≤10th percentile indicating dysplasia (by this metric). Mean NSA overall was 136.5±7.0 degrees. Fifty-one (30.4%) and 20 (11.9%) hips were significantly varus (≤10th percentile) or valgus (≥90th percentile), respectively. Thirty-five hips (20.8%) were the third articulo-trochanteric quartiles or higher suggesting a higher-riding trochanter at baseline. Mean EI was 15.5%±9.0%, while 63 patients (37.5%) had an EI ≥20%. Conclusions: The present study finds significant variation in baseline anatomy in children with early-stage LCPD, including a high prevalence of coexisting acetabular dysplasia as well as high/low NSAs. These variations suggest that the "one-surgery-fits-all" approach may lack specificity for a particular patient; a potentially wiser option may be an anatomic-specific containment operation (eg, acetabular-sided osteotomy for coexisting dysplasia, varus femoral osteotomy for valgus NSA). Level of Evidence: Level IV.